Inclusive Education for Transhumance Groups in Himalayas: Educational Policy Challenge for Nepal - Basnet, Shrestha; Banskota, Mahesh (Journal of Education and Research, 2010)
Nepal’s education policy documents lack a focus as they try to incorporate several issues like modernization and economic growth, to social transformation, social justice, inclusion, equality, social development, human rights etc. This lack of focus has been aggravated by the pathological approach by the international actors through ‘multiple diagnoses’ and ‘multiple prescriptions’. This paper discusses major challenges the educational development stakeholders face in this multiethnic and geographically diverse country where the issue of the inclusion is prominent. DOI: http://dx.doi.org/10.3126/jer.v2i0.7619 Journal of Education and Research Vol. 2, 2010 p.26-29